1986
DOI: 10.1111/j.1747-5457.1986.tb00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic Metamorphism in the Lower Mississippian‐upper Devonian Bakken Shales — Ii: Soxhlet Extraction1

Abstract: In this paper, we report on Soxhlet extraction (and subsequent related analyses) of 39 Lower Mississippian‐Upper Devonian Bakken shales from the North Dakota portion of the Williston Basin, and analyses of 28 oils from the Basin. Because of the influence of primary petroleum migration, no increase in the relative or absolute concentrations of hydrocarbons or bitumen was observed at the threshold of intense hydrocarbon generation (TIHG), or during mainstage hydrocarbon generation in the Bakken shales. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This is often not the case in petroleum systems research, so the availability of a well-calibrated BR o data set provides substantiation for the direct use of BR o in other black shales, particularly those predating land plant evolution. The petroleum geology of the world-class source rocks in the Devonian–Lower Carboniferous Bakken Formation of the Williston Basin has been widely investigated in the last decades, including studies of sedimentology, , paleoenvironment, reservoir characterization, , organic and inorganic geochemistry, and petroleum production. Thermal maturity in the shale members of the Bakken Formation has been historically investigated through VR o studies, , some of which have claimed that the phenomenon of vitrinite reflectance suppression appears to impact VR o measurement. VR o suppression is reported when measured reflectance values are lower than expected relative to thermal maturity as predicted through other means such as comparisons to depth, temperature, or the type of produced petroleum product. Experimental work has shown that VR o suppression can indeed occur under certain conditions, such as in the presence of abundant hydrogen-rich organic matter, and the suppression is postulated to operate through a free radical mechanism which enhances termination reactions and thereby slows the aromatization and rate of increasing structural order in vitrinite .…”
Section: Introductionmentioning
confidence: 99%
“…This is often not the case in petroleum systems research, so the availability of a well-calibrated BR o data set provides substantiation for the direct use of BR o in other black shales, particularly those predating land plant evolution. The petroleum geology of the world-class source rocks in the Devonian–Lower Carboniferous Bakken Formation of the Williston Basin has been widely investigated in the last decades, including studies of sedimentology, , paleoenvironment, reservoir characterization, , organic and inorganic geochemistry, and petroleum production. Thermal maturity in the shale members of the Bakken Formation has been historically investigated through VR o studies, , some of which have claimed that the phenomenon of vitrinite reflectance suppression appears to impact VR o measurement. VR o suppression is reported when measured reflectance values are lower than expected relative to thermal maturity as predicted through other means such as comparisons to depth, temperature, or the type of produced petroleum product. Experimental work has shown that VR o suppression can indeed occur under certain conditions, such as in the presence of abundant hydrogen-rich organic matter, and the suppression is postulated to operate through a free radical mechanism which enhances termination reactions and thereby slows the aromatization and rate of increasing structural order in vitrinite .…”
Section: Introductionmentioning
confidence: 99%